Giant exchange bias induced via tuning interfacial spins in polycrystalline Fe3O4/CoO bilayers. Issue 8 (19th February 2021) - Tian, Fanghua; Li, Yebei; Zhao, Qizhong; Cao, Kaiyan; Wang, Dingchen; Dai, Zhiyong; Yu, Zhonghai; Ke, Xiaoqin; Zhang, Yin; Zhou, Chao; Zuo, Wenliang; Yang, Sen; et al.
Abstract : A giant exchange bias of 9600 Oe was achieved under a magnetic field H FC = 20 kOe in Fe3 O4 /CoO films. Abstract : A giant exchange bias (EB) of 9600 Oe was observed in polycrystalline Fe3 O4 /CoO layers at 10 K after 20 kOe field cooling, and was attributed to the strong exchange coupling formed by the interfacial spins between the polycrystalline Fe3 O4 and the CoO layer. It was found that at 10 K, the magnetic-moment difference (Δ M ) between the zero field cooling curves and field cooling curves first increases and then decreases with the change of the field, and it reaches the maximum value at a field of 20 kOe, which suggests that the interfacial spins can be tuned by the cooling field. Furthermore, other magnetic properties, including field dependence, temperature dependence, and training effects, were investigated, which further confirmed that the interfacial spins play an important role in the EB effect. This work provides a method to tune the magnitude of the EB effect and reveals the mechanism of the dependency of EB on interfacial spins, which could guide the design of giant-EB-effect materials.